2013
DOI: 10.3389/fphys.2013.00252
|View full text |Cite
|
Sign up to set email alerts
|

Factors that regulate insulin producing cells and their output in Drosophila

Abstract: Insulin-like peptides (ILPs) and growth factors (IGFs) not only regulate development, growth, reproduction, metabolism, stress resistance, and lifespan, but also certain behaviors and cognitive functions. ILPs, IGFs, their tyrosine kinase receptors and downstream signaling components have been largely conserved over animal evolution. Eight ILPs have been identified in Drosophila (DILP1-8) and they display cell and stage-specific expression patterns. Only one insulin receptor, dInR, is known in Drosophila and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
224
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(236 citation statements)
references
References 111 publications
(247 reference statements)
5
224
1
6
Order By: Relevance
“…This manipulation caused a moderate loss of sxe2 rhythm, but, as reaper ablation of IPCs is associated with other deleterious phenotypes (Rulifson et al 2002), we examined insulin-like peptide (ILP) signaling directly. The IPCs produce three ILPs-ILP2, ILP3, and ILP5-of which ILP2 is most analogous to mammalian insulin (Nässel et al 2013). To determine whether the effect on sxe2 cycling was due to loss of any of these peptides, we examined mutants lacking ILP2 as well as those lacking ILP2, ILP3, and ILP5 together.…”
Section: Ipcs Represent a Metabolic Clock Output Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…This manipulation caused a moderate loss of sxe2 rhythm, but, as reaper ablation of IPCs is associated with other deleterious phenotypes (Rulifson et al 2002), we examined insulin-like peptide (ILP) signaling directly. The IPCs produce three ILPs-ILP2, ILP3, and ILP5-of which ILP2 is most analogous to mammalian insulin (Nässel et al 2013). To determine whether the effect on sxe2 cycling was due to loss of any of these peptides, we examined mutants lacking ILP2 as well as those lacking ILP2, ILP3, and ILP5 together.…”
Section: Ipcs Represent a Metabolic Clock Output Regionmentioning
confidence: 99%
“…However, the mechanisms underlying rhythmic insulin secretion are not known. Although less complex and not yet implicated in metabolic rhythms, the Drosophila insulin signaling pathway is similar to that in mammals and is important for metabolism (Rulifson et al 2002;Haselton and Fridell 2010;Nässel et al 2013). A major target of insulin in flies is the fat body, a tissue analogous to mammalian liver and adipose tissue with roles in feeding behavior and metabolism (Xu et al 2008;Arrese and Soulages 2010).…”
mentioning
confidence: 99%
“…Metabolic anomalies including increased glucose uptake and excess protein synthesis in the brain have been reported in Fmr1 KO mice, while in the fly (dfmr1), it has been shown that FMRP is required during brain development and may function in neuroblast reactivation by regulating an output of the insulin signaling pathway (48)(49)(50)(51)(52). Metabolic profiling in the Fmr1 KO mice also revealed profound consequences in brain metabolism, which in turn lead to alterations in the metabolic response, along with anomalies in other physiological processes and behaviors (53).…”
Section: Treatmentmentioning
confidence: 99%
“…This fly phenotype closely resembles the aging phenotype. Treatment with stressful agents, such as paraquat exposure which induces oxidative stress, has been shown to increase ISC number and activity in the guts Drosophila [43,44]. Additionally, Okamoto and Nishmura [43] illustrated the existence of a feedback mechanism between DILPs and FOXO.…”
Section: Discussionmentioning
confidence: 99%